Use of pulsed-field gel electrophoresis typing to study an outbreak of infection due to Serratia marcescens in a neonatal intensive care unit. - Miranda, G (1996)
Serratia marcescens is a well-known cause of nosocomial infections and outbreaks, particularly in critically ill neonates and immunocompromised patients. Numerous methods have been proposed for typing. We used pulsed-field gel electrophoresis (PFGE) typing to analyze an outbreak in a neonatal intensive care unit (NICU). We included 23 patient isolates from an outbreak (March to July 1995), and 10 patient isolates from different wards during the same time period. PFGE of whole-cell DNA digested by SpeI was used as a marker of strain identity. The most common presentation of the infection was sepsis in 18 of 23 (78%) neonates. Only four different biotypes were identified; biotype A8d accounted for 84% of the strains. PFGE typing revealed two clones responsible for two different clonal strain dissemination outbreaks from March to July, with 24 patient isolates being pattern A and 4 patient isolates being pattern E. PFGE typing suggests cross transmission between patients in the NICU and other wards. The isolates from 5 other patients showed distinct PFGE patterns. Extensive investigation and cultures failed to identify any environmental or staff reservoir of S. marcescens. This is one of the first reports applying PFGE to the study of S. marcescens, and this method was a useful marker of strain identity. PFGE typing distinguished strains which appeared to be the same by biotyping.